The Placebo Effect in Clinical Trials for Alcohol Dependence: An Exploratory Analysis of 51 Naltrexone and Acamprosate Studies. (24th July 2013) - Litten, Raye Z.; Castle, I‐Jen P.; Falk, Daniel; Ryan, Megan; Fertig, Joanne; Chen, Chiung M.; Yi, Hsiao‐ye
<x xml:space="preserve">Abstract</x> Background The placebo effect often undermines efforts to determine treatment effectiveness in clinical trials. A significant placebo response occurs in alcohol trials, but it is not well understood. The purpose of this study was to characterize the placebo response across multiple naltrexone and acamprosate studies. Methods Fifty‐one trials, 3 with a naltrexone and an acamprosate arm, 31 with at least 1 naltrexone arm, and 17 with at least 1 acamprosate arm, were identified from Cochrane reviews and PubMed search. To be included in this study, patients had to be at least 18 years old, abstinent from alcohol before randomization, and meet a diagnosis of alcohol dependence. Pearson correlation coefficients (rp) and simple linear regression were used to describe the strength of linear relationships between placebo response and treatment effect size. Spearman's rank correlation coefficients (rs) were used to examine the strength of associations between study characteristics and placebo response. Results For the end point measures of percent days abstinent and total abstinence, a negative relationship was evident between placebo response and treatment effect size in the naltrexone trials (rp = −0.55, p < 0.01 and rp = −0.20, p = 0.35, respectively) as well as in the acamprosate trials (rp = −0.45, p = 0.09 and rp = −0.56, p = 0.01, respectively). The placebo response for percent days abstinent was negatively correlated with mean age of participants (rs = −0.42, p = 0.05) across naltrexone trials and positively correlated with publication year (rs = 0.57, p = 0.03) across acamprosate trials. However, these 2 study characteristics were not significantly correlated with treatment effect size. Conclusions The placebo response varied considerably across trials and was negatively correlated with the treatment effect size. Additional studies are required to fully understand the complex nature of the placebo response and to evaluate approaches to minimize its effects.